Correlation of University Students’ Multilingualism in Online Interaction on Instagram and Their Performance in Micro-Teaching Class - Hidayatullah, Riyan; Riyantika, Fajar (Jurnal Pendidikan Progresif, 2024)
Abstract: Correlation of University Students' Multilingualism in Online Interaction on Instagram and Their Performance in Micro-Teaching Class. Objective: The use of multiple languages on social media has been common practice these days. The main objective is to see correlation between their online activities and their micro-teaching performance. This study is focusing on analyzing university students' language use on Instagram and Thread. Method: This study involves 60 students of the Languages and Arts department as its participants. Mixed method is used in this study to obtain comprehensive findings. A survey is conducted to obtain their social media username and general activeness. Then, the researchers run an observation to see the language use of all participants by analyzing the captions they write, the pictures and videos they post, and the comments they give. The final phase involved observation of their micro-teaching performance to see whether the social media interaction somehow manifested during the micro-teaching process. Findings: The result of this study shows a correlation between university students’ language use in the internet and their performance and language style during micro teaching class. Conclusion: It was found that there is a correlation between students’ online interaction on Instagram and their performance in micro teaching class. Keywords: Instagram, multilingualism, online interaction, social media, micro-teaching.DOI: http://dx.doi.org/10.23960/jpp.v14.i1.202401